Implementasi Aplikasi Penilaian Autentik Berbasis Excel oleh Guru dalam Pembelajaran di SMP Negeri 2 Kayangan - Indah Iswantari (Jurnal Paedagogy, 2020)
The purpose of this research is to find out the implementation of authentic excel-based assessment by teachers in learning at SMP Negeri 2 Kayangan. The research method used was descriptive research with 17 subjects. The research instrument used was the monev sheet (monitoring and evaluation). While the data analysis techniques of this study used descriptive qualitative analysis techniques. The results of this study indicate that teachers of SMP Negeri 2 Kayangan have been able to implement authentic based excel assessments very well in their learning. The results of the Monitoring and Evaluation carried out showed that the majority of teachers received a score of 4 (very good) in each assessment indicator.